Lessons from Boston bombings : need for strategic creativity in counter-terrorism - Kumar Ramakrishna (2014)
The recent attacks in Boston offer operational and strategic lessons. Operationally, there is need for better national and international information sharing and understanding of early warning indicators of radicalization. Strategically, the focus of policy responses should be on stronger families, effective self-monitoring of diasporic communities from conflict zones, and the rise of Al Qaedaism.